PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM BERBASIS APLIKASI XAMPP UNTUK MENINGKATKAN MOTIVASI BELAJAR MURID - Nasrul, Nasrul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The background of this study is the dominance of the use of printed teaching materials and conventional methods in Islamic Religious Education (PAI) learning at SMAN 1 Pangkep, so innovation is needed to increase student learning motivation. This study focuses on the development of valid, practical, and effective PAI teaching material products based on the XAMPP application for grade XII students. The method used is research and development (R&D) by adapting the Borg & Gall model through seven stages, including needs analysis, design, expert validation, and product trials. The results of the needs analysis showed a very high interest from students (84%) in application-based teaching materials. The main findings of this study indicate the feasibility of the product being developed. The results of the validation test by media experts (90%) and material experts (97%) stated that the product was